The funerary topography of the Via XVII necropolis in late antiquity (Braga) - Braga, Cristina Maria Vilas Boas (2016)
The present paper aims to analyse archaeological evidence associated with the Roman necropolis of Via XVII, in Braga, with a particular emphasis towards its late antiquity occupation and related with data emerging from the excavations conducted across two main different areas. We intend to reflect over the specific features of the fourth-seventh century’s funerary space of one of the most important necropolis of Bracara Augusta.